2021
DOI: 10.1038/s41467-021-23919-x
|View full text |Cite
|
Sign up to set email alerts
|

Composition and stage dynamics of mitochondrial complexes in Plasmodium falciparum

Abstract: Our current understanding of mitochondrial functioning is largely restricted to traditional model organisms, which only represent a fraction of eukaryotic diversity. The unusual mitochondrion of malaria parasites is a validated drug target but remains poorly understood. Here, we apply complexome profiling to map the inventory of protein complexes across the pathogenic asexual blood stages and the transmissible gametocyte stages of Plasmodium falciparum. We identify remarkably divergent composition and clade-sp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
123
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 73 publications
(131 citation statements)
references
References 103 publications
8
123
0
Order By: Relevance
“…Nonetheless, it should be noted that generally speaking, mitogenome sequencing can be influenced by low sequencing depths caused by low abundance of starting material (derived from difficult to culture parasites bearing a single copy of the organelle). In addition, protocols to obtain pure mitochondrial fractions from many species are lacking, and have only recently been optimized and used for organelle proteome profiling in a few species (Evers et al, 2021;Maclean et al, 2021). These fractions, however, are usually contaminated with plastid DNA.…”
Section: The Mitochondria Of Apicomplexansmentioning
confidence: 99%
See 2 more Smart Citations
“…Nonetheless, it should be noted that generally speaking, mitogenome sequencing can be influenced by low sequencing depths caused by low abundance of starting material (derived from difficult to culture parasites bearing a single copy of the organelle). In addition, protocols to obtain pure mitochondrial fractions from many species are lacking, and have only recently been optimized and used for organelle proteome profiling in a few species (Evers et al, 2021;Maclean et al, 2021). These fractions, however, are usually contaminated with plastid DNA.…”
Section: The Mitochondria Of Apicomplexansmentioning
confidence: 99%
“…Recent "complexome" profiling has shown that the respiratory chain complex IV in T. gondii, which in humans and yeast houses cox1 and cox3, contains peptides of these proteins, and 17 other divergent Apicomplexa-specific proteins (Maclean et al, 2021). Likewise, complexome profiling in Plasmodium revealed both divergent and clade-specific additions to all respiratory chain complexes, and expression of Cox1 and Cox3 peptides (Evers et al, 2021).…”
Section: Mitochondrial Electron Transport Chain Complexes and Mitoribosomesmentioning
confidence: 99%
See 1 more Smart Citation
“…Although its function in mitochondrial fission in these parasites needs to be verified, dispensability of this protein indicates that there are unidentified and more important adaptor proteins that are central to recruitment of the division machinery. Despite a gradually expanding experimental genetics toolbox, ever better imaging resolution, e.g., the successful implementation of expansion microscopy ( 99 ) and focussed ion beam scanning electron microscopy ( 3 ), and novel proteomics-based approaches to study protein-protein interaction and protein complexes ( 10 , 100 ), the studying of such short-lived interactions will remain a significant challenge. Nevertheless, the search for the apicomplexan endosymbiotic organelle division machinery or machineries continues.…”
Section: Discussionmentioning
confidence: 99%
“…The apicomplexan mitochondrion differs greatly from the host mitochondria on a molecular and functional level ( 8 ). One striking difference is that P. falciparum asexual blood stages use their electron transport chain primarily for pyrimidine biosynthesis, rather than ATP synthesis, manifesting in the loss of cristae ( 9 , 10 ). The apicoplast was acquired by secondary endosymbiosis of a red alga but has lost its photosynthetic capacity ( 11 , 12 ).…”
Section: Introductionmentioning
confidence: 99%